A Review of Amine Chemicals Used in the Flotation of Silica - Richard R. Klimpel (Society for Mining, Metallurgy & Exploration, 1999)
This paper reviews some of the factors involved in selecting amine flotation reagents used to remove silica from ores. A comparison is made between the chemical reagent design approaches used to identify flotation reagents that are used to recover silica- and oxygen-containing minerals and the chemical reagents used to recover sulfide minerals. This introduction gives practitioners who are involved with oxide- and carbonate-type minerals and who may not be familiar with sulfide mineral flotation some ideas of the chemical reagent design challenges that exist with froth flotation on a broader scale and why oxide type mineral flotation reagents are what they are. This is followed by several sections that discuss various classes of available amines. The closing sections emphasize that the optimal choice of an amine collector depends not only on that amine's specific chemical characteristics and costs but also on the operating conditions, especially the flotation feed particle size distribution.